Phenomorphological studies in the vegetation of southern Spain. I. Cistus L. - Cabezudo, Baltasar; Navarro, Teresa; Pe?rez Latorre, Andre?s V.; Nieto Caldera, Jose? M.; Orshan, G. (Acta Botanica Malacitana, 1992)
The phenomorphology of five Cistus species was studied in the Montes de Ma?laga range (Ma?laga) of southern Spain. The study sites was visited at least once every month during a whole year. Each of the species was carefully examined, described in the field and representative herbarium specimens collected to form a supporting phenological herbarium. Pheno-morphological diagrams were then made describing the annual cycles of the plants. For three species the diagrams were compared to similar ones made in France and for one to a diagram made also in Israel. The phenophases of flower bud formation, of flowering, of fruit setting, of seed dispersal and of dolichoblast leaf shedding were similar for the species examined in Spain and also in France and Israel. Since no distinction was made between brachyblasts of the current year to those of preceeding ones more variation between species and countries was obtained.